PENGETAHUAN AKUNTANSI, PENGALAMAN USAHA DAN MOTIVASI KERJA TERHADAP PERSEPSI PENGGUNAAN INFORMASI AKUNTANSI PADA PELAKU UMKM DI KOTA MAKASSAR - Suprapty, Eny; Wahyuni, Sry (Universitas Ichsan Sidenreng Rappang, 2025)
This study This Study aims to analyze the effect of accounting knowledge, business experience, and work motivation on the perception of the use of accounting information. Data collection uses primary data with saturated sampling method. The population is MSME players in Makassar City, to be precise at cide market. The result of the questionnaire have been tested for validity and realibity and the classical assumptions in the form of normality assumptions and heteroscedasticity assumptions have been tested methods of data analysis using multiple linear regression techniques. Data were analyzed using SPSS Version 25 The results of this study indicate that Accounting Knowledge, Business Experience and Work Motivation have a significant effect partially or simultaneously on the Use of Accounting Information on MSME Actors in Makassar simultaneously.